APPOINTMENT TO POSITIONS IS THE EDUCATIONAL PART OF THE WORK OF THE TURKESTAN GOVERNOR GENERAL'S COURT (Neo Scientific Peer Reviewed Journal, 2024)
The article is devoted to the administrative-command system that developed in the second half of the 19th – early 20th century after the Russian Empire invaded the history of Turkestan. The main topic of the study is focused on the description of one of the methods of work of the court of the governor-general of Turkestan (the chancery).